India's New Accreditation Law - Agarwal, Pawan (International Higher Education, 2010)
A new accreditation law is currently before the Indian Parliament for approval. The law brings quality in higher education to the center stage. However, given the size and complexity of the system, its implementation is going to be a humongous task. The new law should rely on linking accreditation to government funding and student transfer. A holistic and structured approach with multiple agencies is needed to assure quality for the large and expanding Indian higher education system.